Perkembangan Tradisi Lisan Mangupa Di Kalangan Masyarakat Sumatera Utara - Ika Febriana; Adi Natal Gabriel Siringo-Ringo; Rysta Vara Nurlette (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2023)
This study aims to determine the development of the Mangupa oral tradition among the people of North Sumatra. The method used in this research is descriptive method with a qualitative approach. Data was collected through interviews, observation, and documentation studies. The results of the study show that the Mangupa oral tradition is still being preserved by the people of North Sumatra even though it has undergone several changes. Several factors that influence the development of this tradition include social, economic, and cultural factors. In addition, the support from the government and educational institutions also plays a very important role in maintaining the continuity of the Mangupa oral tradition.